Cultivating positivity to achieve a resilient society: A critical narrative review from psychological perspectives - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2022)
With the rapid speed of globalization and technological breakthroughs, current social issues have become more complex than in past decades. As many issues such as pandemics, terrorism, and interracial conflict are realistically unpredictable, the idea of resilience offers an intuitively plausible and attainable strategy to deal with these potential adversities. The current narrative review explores the cultivation of positive emotions and traits as a plausible way to achieve a resilient society. Based on research in the social and industrial organizational psychology literature, we reviewed the role of positive emotions and traits on resilience. Lastly, we highlight important experiences and interventions that have been shown to be effective in cultivating positivity and discuss several potential considerations and boundary conditions.